Pengembangan Media Digital Berbasis Wordwall Pada Materi Suhu dan Kalor Siswa Kelas V Sekolah Dasar - Trinandita, Adilla; Heryanto, A.; Sunedi, Sunedi (LPPM Institut Pendidikan Nusantara Global, 2024)
In the world of education, teachers are encouraged to innovate and foster creativity to create new and fun learning processes. Problems that often occur include the lack of fun digital-based learning media in elementary schools as well as problems with conventional learning processes. This research aims to develop and design Wordwall-Based Digital Media on Temperature and Heat Material for Class V Elementary School Students that is valid and practical. The type that researchers use is Research and Development (RnD) with the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation. Overall the results from expert validation are in the valid category with a percentage of 82%. Meanwhile, one to one and small group practicality trials were categorized as very practical with percentages of 91% and 93%. It was concluded that Wordwall-Based Digital Media on Temperature and Heat Material for Class V Elementary School Students was valid and practical to use.